Pengaruh pengalaman audit dan tingkat kesulitan penugasan terhadap keakuratan dan keyakinan penentuan auditor pada KAP “Big Four” di Jakarta, Indonesia - Suhardjo, Iwan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the effect of audit experience and difficulty level of assignment on the accuracy and confidence of auditor determination at KAP